FUNGSI SILEK DALAM UPACARA MANJALANG NINIK MAMAK DI KENAGARIAN SIALANG KECAMATAN KAPUR IX KABUPATEN 50 KOTA - Lhaxmi Nuari; Herlinda Mansyur; Susmiarti Susmiarti (SENDRATASIK UNP, 2014)
Abstract This article aimed to describe the function of Silek in ManjalangNinik Mamak ceremony in Sialang, Kapur IX,50 Kota,West Sumatera. This was a qualitative research that was used descriptive method. The object of the research was Silek. The data was collected through observation, interview and documentation. The data was analyzed by classifying the collected data which was match with the conceptual. The result of the research revealed that Silek had a function as a main of traditional ceremony and entertainment. As a main of traditional ceremony, Silek was done before Ninik Mamak entering the ceremony place. On the other hand, Silek also was enjoyed by pesilat and the audients. Kata kunci: fungsi, silek, upacara adat.